ANALISIS SISTEM PENGGERAK PNEUMATIK ALAT ANGKAT KENDARAAN NIAGA KAPASITAS 2 TON - Mohammad Ikhsan Saruna; Rudy . Poeng; Jotje . Rantung (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2013)
Object of this study is a 2-ton capacity manual lifting equipment manufactured by students of Mechanical Enginering Departement of Sam Ratulangi University. The purpose of the study is to develop a pneumatically control lifting equipment as an alternative to the manual controlled as a faster alternative in lifting and lowering the arm of the equipment. The results of the study is a new working system, which operates automatically in the commercial vehicle lifting equipment. The time in lifting is 14,866 sec, while in lowering is 0,084 sec. Key Word: Commercial Vehicle Lifting Equipment, Pneumatic Controls